Bioinformatics : database and algorithms - Gautham, N. (Alpha science, 2007)
Bioinformatics: Databases and Algorithms has two features that distinguish it from others in this genre. First, it seeks to explain some of the basic algorithms in bioinformatics to readers who have little exposure to computer science and mathematics. Second, it deals with structural bioinformatics in greater depth than most other books. The emphasis of this book is on algorithms, though databases have not been entirely neglected, and they have a whole chapter to themselves. Also much attention is given to structural bioinformatics.